The Role of Secretory Autophagy in Zika Virus Transfer through the Placental Barrier - Zhang, Zhong-Wei; Li, Zi-Lin; Yuan, Shu (Frontiers in Cellular and Infection Microbiology, 2017)
Recent studies indicated that the Zika virus genome could be detected in the amniotic fluid and the fetal brain, which confirms that the virus can cross the placental barrier. Secretory autophagy or exosome pathways may participate in this virus transfer. Autophagy modulators regulate autophagosome formation or membrane fusion with lysosomal vesicles and therefore inhibit viral nucleocapsid releasing or virus transfer to the fetus hypothetically. However, some autophagy modulators may enhance virus replication. Autophagy inhibitors may arrest placental devel¬opment; while exaggeration of autophagy in human placenta may be associated with the fetal growth restriction. Therefore, autophagy modulators should be used carefully due to their complex clinical effects. Alternatively, exosome-specific inhibitors might be also considered, although their safety of both maternal and fetal conditions must be carefully assessed before any advancement to human clinical trials.